Borane-induced ring closure reaction of oligomethylene-linked bis-allenes. Issue 6 (3rd January 2020) - Tao, Xin; Škoch, Karel; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract : The borane induced cyclization of the bis-allene followed by reaction with two molar equivalents of allene gives the functionalized decalin product. Abstract : The trimethylene-linked bis-allene 3a reacts with Piers' borane [HB(C6 F5 )2 ] by a hydroboration/allylboration sequence to generate the cyclization product 5a . Its pyridine adduct was isolated and characterized by X-ray diffraction. Compound 5a undergoes a typical frustrated Lewis pair 1, 2-P/B alkene addition reaction with PPh3 to give the heterobicyclic bridged olefinic zwitterionic product 9a . The tetramethylene-linked bis-allene 3b and its phenylene annulated analogue 3c react with HB(C6 F5 )2 to give the analogous seven-membered ring products 5b, c under mild conditions. The cyclization product 5a undergoes a series of sequential allylboration reactions with two equivalents of allene followed by ring-closure to give the four-component coupling product 12a . It undergoes FLP addition to an exo-methylene group upon treatment with PPh3 . Compound 12a is oxidatively converted to the boron-free alcohol.